A METHOD FOR OBTAINING PRECIPITATING SERUMS FOR THE DETECTION OF HUMAN SEMINAL FLUID USED IN THE STUDY OF PHYSICAL EVIDENCE IN FORENSIC BIOLOGICAL LABORATORIES (World Bulletin of Management and Law, 2023)
Serological research methods, while being considered highly effective, are affordable in comparison with morphological methods for studying semen stains on physical evidence and do not require large financial costs. In this work, on the basis of scientific research, a new scheme for obtaining precipitating sera that specifically reacts to human seminal fluid, intended for use in forensic laboratories, obtained by hyperimmunization of animal producers, has been developed
Keywords: physical evidence; human seminal fluid; precipitating sera; serological methods